ANALISIS PEMASARAN PADA AGROINDUSTRI TEMPE DI KOTA PALANGKA RAYA - Hamim Thohari; Jhon Wardie; Revi Sunaryati (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2018)
This research was conducted in the City of Palangka Raya. The location of the research was done intentionally (purposive sampling) with the consideration that as the capital city of Central Kalimantan Province, in Palangka Raya City there was a lot of enthusiasm and became the center of tempe agroindustry production. Determination of tempe agroindustry respondents was conducted using the census method (census sampling), which is by taking all tempe agro-industry entrepreneurs (16 entrepreneurs) in Palangka Raya City. Furthermore, the determination of the tempe marketing institutions which includes large wholesalers and retailers is carried out by a snowball sampling method. Data collected in this study are primary data and secondary data. Tempe marketing in Palangka Raya City consists of three marketing channels and the marketing institutions involved are wholesalers and retailers. The total marketing costs of tempe per pack in the marketing channel patterns I, II and III are Rp. 0,-, Rp. 500,- and Rp. 1,000,- and also Rp. 1,200,-. The total marketing margin of tempe per pack in the marketing channel pattern I is Rp. 900,- for small sizes, Rp. 1,100,- for medium size and Rp. 1,210,- for large sizes. In the marketing channel pattern II is Rp. 1,000,- for small size, and Rp. 2,000,- for medium and large sizes. In the marketing channel pattern III of Rp. 3,000,- for small, medium and large sizes. The total profit for marketing tempe per pack in the marketing channel pattern I is Rp. 900,- for small tempe, Rp. 1,100,- for medium-sized tempe and Rp. 1,210,- for large tempe. In the marketing channel pattern II is Rp. 500,- for small tempe, Rp. 1,000,- for medium and large tempe. In the marketing channel pattern III of Rp. 1,800,- for small, medium and large sizes tempe.